Blood Biomarkers Alterations with Administration of Propofol for Anaesthesia Maintenance during Long term Oral and Maxillofacial Surgeries - Dahi, Mastaneh; Pourdanesh, Fereydoun; Samieirad, Sahand; Morad, Golnaz; Khojasteh, Arash (Journal of Dental School, 2019)
Objective: This prospective study performed to evaluate blood biomarkers alterations with administration of propofol for maintenance of anaesthesia during long oral and maxillofacial surgeries in order to estimate the risk of Propofol Infusion Syndrome (PRIS). This rare syndrome often would be happened in long duration or high dose infusion which is characterized by the combination of metabolic acidosis, acute bradycardia and/or asystole, and rhabdomyolysis and can be fatal. Methods: Patients undergoing maxillofacial surgeries (>3h) were the subjects of this quasi experimental prospective clinical trial study. Induction of anaesthesia was performed with midazolam 0.025 mg/kg, fentanyl 2 µg/kg, thiopental sodium 5 mg/kg, and atracurium 0.5 mg/kg. Infusion of propofol was initiated (100 µg/kg/min) for maintenance of anesthesia. Serum potassium level, creatine kinase, lactate and blood PH, were evaluated at baseline, and at 2, 4, 6 hours following the initiation of propofol infusion. Generalized estimating equation was used to evaluate the longitudinal changes for each of the evaluated biomarkers. The relation between the biomarkers and the following factors were appraised by using covariance linear (enter mode) regression analysis: age, gender, weight, administered dose of dexamethasone and epinephrine, duration of surgery, and a history of trauma prior to surgery. Results: A total of 55 participants, 31 women and 24 men, were studied. The mean duration of surgery was 4.8(1) hours. Despite the rise in the level of potassium and creatine kinase and the reduction of blood PH, no case of hyperkalemia or severe metabolic acidosis was observed. Serum lactate level gradually increased to higher than normal in few patients; though did not necessitate any intervention. All alterations were statistically significant. Potassium and creatine kinase level at baseline had relation to pre-surgical trauma. Conclusion: Maintenance of anaesthesia with 100 µg/kg/min propofol along with administration of low-dose epinephrine and dexamethasone did not cause clinically important alterations in blood biomarkers during long-duration maxillofacial surgeries and might not cause PRIS.